Salmonella antimicrobials inherited and the non-inherited resistance: mechanisms and alternative therapeutic strategies - Zhou, Kaixiang; Sun, Lei; Zhang, Xuehua; Xu, Xiangyue; Mi, Kun; Ma, Wenjin; Zhang, Lan; Huang, Lingli (Frontiers in Microbiology, 2023)
Salmonella spp. is one of the most important foodborne pathogens. Typhoid fever and enteritis caused by Salmonella enterica are associated with 16–33 million infections and 500,000 to 600,000 deaths annually worldwide. The eradication of Salmonella is becoming increasingly difficult because of its remarkable capacity to counter antimicrobial agents. In addition to the intrinsic and acquired resistance of Salmonella, increasing studies indicated that its non-inherited resistance, which commonly mentioned as biofilms and persister cells, plays a critical role in refractory infections and resistance evolution. These remind the urgent demand for new therapeutic strategies against Salmonella. This review starts with escape mechanisms of Salmonella against antimicrobial agents, with particular emphasis on the roles of the non-inherited resistance in antibiotic failure and resistance evolution. Then, drug design or therapeutic strategies that show impressive effects in overcoming Salmonella resistance and tolerance are summarized completely, such as overcoming the barrier of outer membrane by targeting MlaABC system, reducing persister cells by limiting hydrogen sulfide, and applying probiotics or predatory bacteria. Meanwhile, according to the clinical practice, the advantages and disadvantages of above strategies are discussed. Finally, we further analyze how to deal with this tricky problems, thus can promote above novel strategies to be applied in the clinic as soon as possible. We believed that this review will be helpful in understanding the relationships between tolerance phenotype and resistance of Salmonella as well as the efficient control of antibiotic resistance.